The Downregulation of c19orf12 Negatively Affects Neuronal and Musculature Development in Zebrafish Embryos - Mignani, Luca; Zizioli, Daniela; Borsani, Giuseppe; Monti, Eugenio; Finazzi, Dario (Frontiers in Cell and Developmental Biology, 2020)
Mitochondrial membrane Protein Associated Neurodegeneration (MPAN) is a rare genetic disorder due to mutations in C19orf12 gene. In most cases, the disorder is transmitted as an autosomal recessive trait and the main clinical features are progressive spastic para/tetraparesis, dystonia, motor axonal neuropathy, parkinsonisms, psychiatric symptoms, and optic atrophy. Besides iron accumulation in the globus pallidus and substantia nigra, the neuropathology shows features also observed in Parkinson’s Disease brains, such as α-synuclein-positive Lewy bodies and hyperphosphorylated tau. Mutations in the gene have been found in other neurodegenerative disorders, including PD, hereditary spastic paraplegia, pallido-pyramidal syndrome, and amyotrophic lateral sclerosis. The biological function of C19orf12 gene is poorly defined. In humans, it codes for two protein isoforms: the longer one is present in mitochondria, endoplasmic reticulum, and contact regions between mitochondria and ER. Mutations in the gene appear to be linked to defects in mitochondrial activity, lipid metabolism and autophagy/mitophagy. To increase the available tools for the investigation of MPAN pathogenesis, we generated a new animal model in zebrafish embryos. The zebrafish genome contains 4 co-orthologues of human C19orf12. One of them, located on chromosome 18, is expressed at higher levels at early stages of development. We downregulated its expression by microinjecting embryos with a specific ATG-blocking morpholino, and we analyzed embryonal development. Most embryos showed morphological defects such as unsettled brain morphology, with smaller head and eyes, reduced yolk extension, tilted and thinner tail. The severity of the defects progressively increased and all injected embryos died within 7 days post fertilization. Appropriate controls confirmed the specificity of the observed phenotype. Changes in the expression and distribution of neural markers documented a defective neuronal development, particularly evident in the eyes, the optic tectum, the midbrain-hindbrain boundary; Rohon Beard and dorsal root ganglia neurons were also affected. Phalloidin staining evidenced a significant perturbation of musculature formation that was associated with defective locomotor behavior. These data are consistent with the clinical features of MPAN and support the validity of the model to investigate the pathogenesis of the disease and evaluate molecules with potential therapeutic effect.